81.8k views
0 votes
Lim_(x-1)(2x^(2)-9x+9)/(x-3)=

User DAnglin
by
5.6k points

1 Answer

4 votes

Answer:


\lim_(x\to 1)(2x^2-9x+9)/(x-3)=-1.

Explanation:

Consider the given limit problem is


\lim_(x\to 1)(2x^2-9x+9)/(x-3)=?

We need to find the value of given limit problem.

Taking limit, we get


\lim_(x\to 1)(2x^2-9x+9)/(x-3)=(2(1)^2-9(1)+9)/((1)-3)


\lim_(x\to 1)(2x^2-9x+9)/(x-3)=(2-9+9)/(-2)


\lim_(x\to 1)(2x^2-9x+9)/(x-3)=(2)/(-2)


\lim_(x\to 1)(2x^2-9x+9)/(x-3)=-1

Therefore,
\lim_(x\to 1)(2x^2-9x+9)/(x-3)=-1.

User Martin Costello
by
6.0k points